2016
DOI: 10.1590/s1679-45082016rb3594
|View full text |Cite
|
Sign up to set email alerts
|

Application of botulinum toxin to treat sialorrhea in amyotrophic lateral sclerosis patients: a literature review

Abstract: Amyotrophic lateral sclerosis is a progressive and fatal neurodegenerative disease characterized by the degeneration of motor neurons, which are the central nervous system cells that control voluntary muscle movements. The excessive salivation (sialorrhea) is present in approximately 50% of amyotrophic lateral sclerosis cases. Thus, some alternative therapeutic methods are sought, such as anticholinergic drugs and surgery. Recently the use of botulinum toxin applied at a midpoint of the salivary glands, often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…in the submandibular, when applied [9]. In the study, both brands of botulinum toxin available at the hospital were used-Botox®, Dysport®, considering the equivalence of drugs.…”
Section: Methodsmentioning
confidence: 99%
“…in the submandibular, when applied [9]. In the study, both brands of botulinum toxin available at the hospital were used-Botox®, Dysport®, considering the equivalence of drugs.…”
Section: Methodsmentioning
confidence: 99%
“…O tratamento convencional consiste na utilização de drogas colinérgicas, as quais podem desencadear retenção urinária e cefaleia (Pieh & Gottlob, 2000como citado em Oliveira et al, 2016. Para pacientes com a doença em estágios iniciais, a remoção de uma das glândulas salivares é uma abordagem promissora, porém submete o doente aos riscos anestésicos (Oliveira et al, 2016). A utilização da toxina botulínica nesse quadro é eficiente nas glândulas parótidas e submandibulares, com bons resultados entre o segundo e o terceiro mês de terapêutica (Costa & Ferreira, 2008como citado em Oliveira & Valadão, 2018.…”
Section: Sialorreia Ou Ptialismounclassified
“…Addition of a methyl group in the ortho (8) and meta (9) position produced a ~2-fold increase in potency whereas the para substituted compound 10 exhibited minimal effect on the potency. Of note, addition of an ethyl group (11) in the para position resulted in a ~2-fold loss in potency when compared to unsubstituted benzylamine 7. With the docked structure of 7 (Figure 2D) in mind, this suggested that 11 may be too large, potentially clashing with Phe192 deep within the hydrophobic sub-pocket.…”
mentioning
confidence: 99%